Value-Creating Global Citizenship Education Engaging Gandhi, Makiguchi, and Ikeda as Examples - Sharma, Namrata (Palgrave Studies in Global Citizenship Education and Democracy, 2018)
This book fills an existing gap within the practice of global citizenship education by offering Asian perspectives. In this book, Soka or value-creating education developed by the Japanese educators, Tsunesaburo Makiguchi (1871-1944) and Daisaku Ikeda (b. 1928) is compared to the ideas of the Indian political leader Mahatma Gandhi (1869-1948). This study of their respective thoughts and movements has a significant bearing on the three domains of learning within the global citizenship education conceptual dimensions of UNESCO - the cognitive, socio-emotional, and behavioral. This book deftly combines theoretical discussions with themes and suggestions for practice and future research. .